2022
DOI: 10.3390/polym14061079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Type and Content on Mechanical Property and Lapping Machinability of Fiber-Reinforced Polyetheretherketone

Abstract: Polyetheretherketone (PEEK) is a novel polymer material with excellent material properties. The hardness and strength of PEEK can be further improved by introducing fiber reinforcements to meet the high-performance index of the aerospace industry. The machinability will be influenced when the material properties change. Therefore, it is crucial to investigate the influence of material properties of the fiber-reinforced PEEK on machinability. In this paper, the main materials include pure PEEK, short carbon-fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, adding carbon fibers could effectively reduce the degree of material swelling on both sides of the PEEK matrix grooves and improve the grinding surface quality. On the other hand, the CF30/PEEK’s nano-indentation curve was higher than CF10/PEEK [ 21 ], indicating that CF30/PEEK had a better deformation resistance. As seen in Figure 7 and Figure 8 , the grooves on the surface of CF30/PEEK were shallower than those on CF10/PEEK after grinding with the same grit size grinding wheel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, adding carbon fibers could effectively reduce the degree of material swelling on both sides of the PEEK matrix grooves and improve the grinding surface quality. On the other hand, the CF30/PEEK’s nano-indentation curve was higher than CF10/PEEK [ 21 ], indicating that CF30/PEEK had a better deformation resistance. As seen in Figure 7 and Figure 8 , the grooves on the surface of CF30/PEEK were shallower than those on CF10/PEEK after grinding with the same grit size grinding wheel.…”
Section: Discussionmentioning
confidence: 99%
“…However, both CF30/PEEK and GF30/PEEK were weak plastic materials. Thus, based on the tensile test results of Gao et al [ 21 ], this paper sorted the minimum cutting thickness values of different materials by calculating the ratio of the elastic modulus to tensile strength and divided the value of k into five different values corresponding to five different materials in the test. Table 6 shows the value results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang et al 15 compared the reinforcing effect of various fibers on PEEK matrix and found that carbon fibers, glass fibers, and TiO 2 can effectively improve the tensile strength of the matrix. Gao et al 16 further analyzed the mechanical properties of different components and types of fiber-reinforced PEEK materials by controlling the fiber type and content. These studies are of great help in understanding the mechanical properties of PEEK composite materials, and based on the experimental results, more accurate constitutive models can be constructed to evaluate the influence of strain rate and temperature on material performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the different recycling methodologies, and their inherent advantages or disadvantages, mechanical recycling is the most technologically mature CFRP recycling method, which generally consists of reducing the material size to be further incorporated as a reinforcement or filler into new matrices (e.g., polymers, cement, among others) (Butenegro et al, 2021), (Giorgini et al, 2020), (Meng et al, 2020), (Oliveux et al, 2015;Vincent et al, 2019;Gao et al, 2022). Beyond mechanical methods, chemical recycling is a promising and complementary alternative to overcome the challenges inherent to traditional CFRP composites, allowing the recovery of valuable CFs through the depolymerization of the network structure by the cleavage of specific bonds presented in cured thermosets.…”
mentioning
confidence: 99%